2018
DOI: 10.1007/s00394-018-1823-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of dietary nitrate intake from vegetables with cardiovascular disease mortality: a prospective study in a cohort of older Australians

Abstract: In older Australian men and women, vegetable nitrate intake was inversely associated with CVD mortality, independent of lifestyle and cardiovascular risk factors. These findings confirm a recent report that intake of vegetable nitrate lowers the risk of CVD mortality in older women and extend these findings to older men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 73 publications
3
47
0
Order By: Relevance
“…On average, women within our sample were consuming approximately 61 mg/day total nitrate and 48 mg/day vegetable nitrate at baseline. This level of nitrate intake was markedly lower than mean nitrate intakes estimated in previous Australian based cohort studies, including the Calcium Intake Fracture Outcome Study (CAIFOS) (total nitrate ~79 mg/day; vegetable nitrate ~67mg/day) [41] and the Blue Mountains Eye Study cohort (BMES) (total nitrate ~129 mg/day; vegetable nitrate ~110 mg/day) [42]. These large differences in estimated nitrate intakes have occurred despite using the same nitrate databases to estimate intakes [19,28,29,30].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…On average, women within our sample were consuming approximately 61 mg/day total nitrate and 48 mg/day vegetable nitrate at baseline. This level of nitrate intake was markedly lower than mean nitrate intakes estimated in previous Australian based cohort studies, including the Calcium Intake Fracture Outcome Study (CAIFOS) (total nitrate ~79 mg/day; vegetable nitrate ~67mg/day) [41] and the Blue Mountains Eye Study cohort (BMES) (total nitrate ~129 mg/day; vegetable nitrate ~110 mg/day) [42]. These large differences in estimated nitrate intakes have occurred despite using the same nitrate databases to estimate intakes [19,28,29,30].…”
Section: Discussionmentioning
confidence: 74%
“…On the other hand, we expect there are two major reasons why our cohort has lower estimated nitrate intakes than those reported by the BMES, including differences in the FFQ tool and cohort population. Unlike the ALSWH and CAIFOS cohorts which use the 74 item DQES and include only female participants, the BMES includes female and male participants aged >45 years old, and assessed diet using a 145 item FFQ [42]. This is an important factor to consider in this context, given men and women differ in their preferences for food items and consumption amounts, thus it is reasonable to expect that gender differences could be driving these inconsistencies [43].…”
Section: Discussionmentioning
confidence: 99%
“…This study on the other hand calculated nitrate intake using the updated US Department of Agriculture food composition tables, which is most appropriate given that this study has been conducted in an American population. In light of these differences, it is not surprising that the nitrate intake in the NHS have been estimated at levels markedly higher (mean nitrate intake: 152 mg/d) than those reported in the Australian-based cohorts (Blekkenhorst et al (21) mean nitrate: 80 mg/d; Liu et al (22) mean nitrate: 130 mg/d). However, our mean nitrate intake estimations are similar to those previously reported in the NHS by Kang et al (42) (mean nitrate intake: 142 mg/d), in which higher dietary nitrate intake were associated with a lower primary open-angle glaucoma risk.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, Liu et al (22) prospectively investigated the association of nitrate intake with CVD mortality in a sample of 2229 Australian men and women aged ≥49 years, followed up for 14 years. Participants consuming the highest (>137•8 mg/d) compared with the lowest (<69•5 mg/d) quartile for vegetable nitrate intake were observed to be at a 37 % lower hazards of CVD mortality (HR: 0•63, 95 % CI 0•41, 0•95) (22) . In light of these previously published findings, it is perplexing to note that despite observing a similar trend to Blekkenhorst et al (21) in the age-adjusted model, the fully adjusted model was not statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several investigations have demonstrated that dietary supplementation with inorganic nitrate, typically in doses between 4 and 12 mmol/day (~250–750 mg/day), can reduce blood pressure (BP),13–17 improve endothelial function14 17 18 and, at least in recreationally active and moderately trained individuals, enhance exercise performance 19–24. In addition, several recent observational studies have linked increased nitrate intake with reduced risk of cardiovascular disease mortality,25 atherosclerotic vascular disease26 and ischaemic cerebrovascular disease 27…”
Section: Introductionmentioning
confidence: 99%